2013
DOI: 10.1080/00207594.2013.804190
|View full text |Cite
|
Sign up to set email alerts
|

The physical environment and child development: An international review

Abstract: A growing body of research in the United States and Western Europe documents significant effects of the physical environment (toxins, pollutants, noise, crowding, chaos, housing, school and neighborhood quality) on children and adolescents’ cognitive and socioemotional development. Much less is known about these relations in other contexts, particularly the global South. We thus briefly review the evidence for relations between child development and the physical environment in Western contexts, and discuss som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 246 publications
(651 reference statements)
8
135
0
6
Order By: Relevance
“…A cross sectional study in Baghdad City, Iraq using the Colored Raven's Matrices showed that children that performed poorly on the Colored Raven's Matrices lived in stressful environments [15]. Therefore, it would be more meaningful if results of intelligence tests conducted in environments similar to the participants are used in their interpretation [14,15]. Studies on cognitive functioning have been conducted in different parts of the world within different environments but baseline data do not exist for students attending Wesley School for the hearingimpaired in Lagos, Nigeria or for hearing-impaired children in Nigeria.…”
Section: Environment and Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…A cross sectional study in Baghdad City, Iraq using the Colored Raven's Matrices showed that children that performed poorly on the Colored Raven's Matrices lived in stressful environments [15]. Therefore, it would be more meaningful if results of intelligence tests conducted in environments similar to the participants are used in their interpretation [14,15]. Studies on cognitive functioning have been conducted in different parts of the world within different environments but baseline data do not exist for students attending Wesley School for the hearingimpaired in Lagos, Nigeria or for hearing-impaired children in Nigeria.…”
Section: Environment and Intelligencementioning
confidence: 99%
“…A lot of research on environment and intelligence level has been conducted in countries that rank high on the United Nations Development Program (UNDP) Human Development Index and the results were used to interpret level of intelligence on people from countries that rank low on the Human Development Index [14]. Environmental factors impact cognitive attainment.…”
Section: Environment and Intelligencementioning
confidence: 99%
“…Research investigating effects of school quality on cognitive development and how different factors shape cognitive skills has originated mainly from the United States and Western Europe (Evans, 2006; Ferguson, Cassells, MacAllister, & Evans, 2013). Over the past three decades, most of these studies of school effects on student achievement in LMIC (Glewwe, Hanushek, Humpage, & Ravina, 2011; Riddell, 2008; Scheerens, 2001) have examined the impact of school structure and organization, physical and human resources (e.g., class size, teacher training and teacher salaries, availability of textbooks, general facilities and equipment; Fuller, 1987; Fuller & Clarke, 1994; Lee & Zuze, 2011) and instructional processes (e.g., teacher's use of instructional time, the amount and type of curriculum covered; Fuller & Heyneman, 1989).…”
Section: School Effects In Lmic and Sub-saharan Africamentioning
confidence: 99%
“…Although environmental cues provide a major source of information to guide development, and capturing these cues is both essential and adaptive, such reliance opens a window of potential vulnerability when harsh early conditions trigger developmental trade-offs or direct impairments with subsequent cumulative long-term costs to function and well-being (Hanson and Gluckman; Hochberg et al, 2011). Hence, early exposures to adversity–both physical (such as crowding, poverty) and psychosocial (such as neglect or abuse, parental harshness or conflict) have been linked to later mental and physical health risk (Ferguson et al, 2013; Grant et al, 2014; Miller et al, 2011). Developmental neuroscience has found that the brain is sensitive not only to nutrition but also to pattern and quality of early experience (Fox et al; Petrosini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%